Association of macrophage and lymphocyte infiltration with outcome in canine osteosarcoma. (19th September 2018) - Withers, Sita S.; Skorupski, Katherine A.; York, Daniel; Choi, Jin W.; Woolard, Kevin D.; Laufer‐Amorim, Renee; Sparger, Ellen E.; Rodriguez, Carlos O.; McSorley, Stephen J.; Monjazeb, Arta M.; Murphy, William J.; Canter, Robert J.; et al.
Abstract : Immunotherapeutic strategies have shown promise for the treatment of canine osteosarcoma (cOSA). Very little is known about the immune microenvironment within cOSA, however, limiting our ability to identify potential immune targets and biomarkers of therapeutic response. We therefore prospectively assessed the disease‐free interval (DFI) and overall survival time (ST) of 30 dogs with cOSA treated with amputation and six doses of adjuvant carboplatin. We then quantified lymphocytic (CD3+, FOXP3+) and macrophage (CD204+) infiltrates within the primary tumours of this cohort using immunohistochemistry, and evaluated their association with outcome. Overall, the median DFI and ST were 392 and 455 days, respectively. The median number of CD3+ and FOXP3+ infiltrates were 45.8 cells/mm 2 (4.6‐607.6 cells/mm 2 ) and 8.5 mm 2 (0‐163.1 cells/mm 2 ), respectively. The median area of CD204+ macrophages was 4.7% (1.3%‐23.3%), and dogs with tumours containing greater than 4.7% CD204+ macrophages experienced a significantly longer DFI ( P = 0.016). Interestingly, a significantly lower percentage of CD204+ macrophages was detected in cOSA arising from the proximal humerus compared to other appendicular bone locations ( P = 0.016). Lymphocytic infiltrates did not appear to correlate with outcome in cOSA. Overall, our findings suggest that macrophages may play a role in inhibiting cOSA progression, as has been suggested in human osteosarcoma.